2021
DOI: 10.1155/2021/6666089
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Development and Supervision of Robo‐Advisors under Digital Financial Inclusion in Complex Systems

Abstract: With the rapid development of the market economy, there are more and more projects in the financial industry, and their complexity and technical requirements are getting higher and higher. The development of computer technology has promoted the birth of robot consultants, and it is of great significance to use robot consultants to manage and supervise financial industry projects. In order to further analyze the development and supervision of robo-advisors under the digital inclusive financial system, this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Therefore, from the perspective of what should be and the development trend of intelligent investment advisers in the future, China's intelligent investment advisers can be defined as providing customers with personalized investment advice services matching their portraits based on modern financial theories and models and relying on emerging technologies dominated by artificial intelligence asset management services. After combing the risk sources of the legal supervision mechanism of the recommendation algorithm through the big data analysis method, literature [22] found that the risks in traditional financial activities still continue to the intelligent investment adviser, and the legal supervision mechanism of the recommendation algorithm will even amplify the traditional risks, resulting in more serious consequences. Moreover, as the service basis of the legal supervision mechanism of recommendation algorithm, algorithm technology also brings challenges to intelligent investment advisory services.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, from the perspective of what should be and the development trend of intelligent investment advisers in the future, China's intelligent investment advisers can be defined as providing customers with personalized investment advice services matching their portraits based on modern financial theories and models and relying on emerging technologies dominated by artificial intelligence asset management services. After combing the risk sources of the legal supervision mechanism of the recommendation algorithm through the big data analysis method, literature [22] found that the risks in traditional financial activities still continue to the intelligent investment adviser, and the legal supervision mechanism of the recommendation algorithm will even amplify the traditional risks, resulting in more serious consequences. Moreover, as the service basis of the legal supervision mechanism of recommendation algorithm, algorithm technology also brings challenges to intelligent investment advisory services.…”
Section: Related Workmentioning
confidence: 99%
“…For the steady development of colleges and universities, establishing a perfect financial management system and effective financial management is crucial [1][2]. At present, the traditional financial management mode of colleges and universities can no longer meet the financial management requirements of colleges and universities in the context of information technology, and there are many shortcomings [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, many studies on digital financial inclusion have emerged. In the year 2021 alone, many studies examined digital financial inclusion in relation to economic growth (Ahmad et al, 2021), entrepreneurship (Baker, 2021), urban-rural income gap (Ji et al, 2021), poverty reduction (Wang and Fu, 2021), investment diversification (Lu et al, 2021), complex systems (Dai, 2021), research and development (Sun et al, 2021), etc. Despite the increasing number of studies on digital financial inclusion, digital financial inclusionin terms of its meaning, goal, components, instruments and regulatory issues is not generally understood.…”
Section: Introductionmentioning
confidence: 99%